Development of Cu-based multicomponent quantum nanostructures - Bai, Xue (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
The main goal of this project was to develop novel Cu-based multicomponent quantum nanostructures with distinct morphologies and optical properties and explore their potential applications as materials for luminescent solar concentrators. Chapter 1 presents a literature review and background knowledge on the photophysics, synthesis and applications of Cu-based multicomponent quantum dots, particularly heterostructured quantum dots. Chapter 2 provides the synthetic and experimental protocols used in this project. The characterization techniques and equipment employed are also detailed. Chapter 3 presents the synthesis and characterization of Cu-based spherical CIZS/ZnS core/shell and CIZS/ZnS/ZnS core/shell/shell quantum heterostructures. The Cu-In-Zn-S core was prepared using a hot injection technique by injecting the anion precursor solution into the cation precursor solution which loaded in a three-neck round-bottom flask. Then a seeded growth method was employed to coat the first ZnS shell onto the preformed CIZS core to obtain the CIZS/ZnS core/shell heterostructures, and then the second ZnS shell to get the CIZS/ZnS/ZnS QDs with higher quantum yields. The obtained quantum nanostructures were fully characterized by various instrumental techniques. Chapter 4 describes the synthesis and characterization of a novel, highly fluorescent Cu-based Cu-In-(Zn)-S/ZnS ?ice-cream? like nanoheterostructures. The Cu-In-S seeds were prepared with a straightforward heating up technique, which was followed with the shell coating using a seeded growth method. This sample was thoroughly characterized using a range of microscopy and spectroscopic techniques. Chapter 5 reports the synthesis of the fluorescent Cu-based Cu-In-Zn-Se/Cu-In-Zn-S/ZnS core/shell/shell heteronanonail structures. The hot injection technique was employed to prepare the CIZSe seeds, which was followed by the shell coating of CIZS shell and then ZnS shell with the seeded growth methods. Au particles were deposited onto the surface of the preformed CIZSe/CIZS/ZnS nanonails resulting in the unique Au-CIZSe/CIZS/ZnS nanocomposites. Chapter 6 is dedicated to the incorporation of highly fluorescent Cu-based QDs into PMMA matrix for the building of luminescent solar concentrators. Four types of Cu-based QDs have been embedded into PMMA polymer block, including (1) CIZS/ZnS heterostructured QDs with relatively thin ZnS shell, (2) CIZS/ZnS/ZnS heterostructured QDs with thicker ZnS shell, (3) CIZS/ZnS/ZnS heterostructured QDs with the thickest ZnS shell and (4) alloyed CIZS/ZnS QDs. Detailed study of the obtained LSCs have been performed. Finally, chapter 7 outlines the conclusions of the entire work, presents some preliminary studies and future plans for our work.
APPROVED
Keywords: Cu-based, quantum dots, fluorescence, quantum yields, nanostructures